Learning what our target audiences think and do: extending segmentation to all four bases - Anna Kitunen; Sharyn Rundle-Thiele; Mohammad Kadir; Abi Badejo; George Zdanowicz; Megan Price (BMC, 2019)
Abstract Background While acknowledged as one of social marketing's necessities, limited reporting of segmentation exists. The current study seeks to extend segmentation drawing on all four segmentation bases within the context of Queensland young adult sexual health behaviour. Methods An online survey was used to collect data from 15 to 29 year old people in Queensland, Australia. Data collection was undertaken online to capture the broader population of young adults and in person on campuses to gather data from students who were currently enrolled at University. Quotas were set to ensure a broad representation was attained reflecting the States demography. Results Two-step cluster analysis revealed three different segments. The most important variables in segment formation were age, household type, experience of risky sexual encounters and previously being tested or treated for sexually transmissible infections (STIs). The results suggest that demographic and behavioural variables were the most effective in segment definition. Conclusions This study investigated young people aged 15-29 in Queensland, Australia to examine group differences drawing from four bases. This study revealed three distinct segments in a sexual health context and highlighted the importance of behavioural variables in segment formation, insight and understanding.